A retrospective audit of mitral valve repair surgery at Tygerberg Hospital - Naili, M.Al; Herbst, P.G.; Doubell, A.F.; Janson, J.J.; Pecoraro, A.J.K. (SA Heart Journal, 2018)
Background: Mitral valve repair is well established as the preferred treatment modality for the majority of patients with degenerative mitral valve disease requiring intervention. Valve repair offers a distinct event-free survival advantage compared with replacement with either a bioprosthetic or mechanical valve. At present, there are little data available on the management and outcome of mitral valve repair in South Africa. The aim of this study is to describe and compare the indications, specific pathology and outcomes of patients accepted for mitral valve repair. Internationally published figures for peri-operative mortality are less than 2% for degenerative mitral regurgitation, with a freedom from mitral valve reoperation of 94% at 10 years. Methods: All patients referred for mitral valve repair at Tygerberg Hospital, Cape Town, South Africa, between 1 December 2010 and 30 June 2015, were retrospectively included. Demographic characteristics, cardiovascular risk factors, pre-operative (NYHA) functional class, the pre- and post-operative transthoracic and transoesophageal echocardiograms, immediate in hospital mortality and 6-month post-surgical mortality and functional class were analysed. Repair failure was defined as either intra-operative conversion to MVR or need for reoperation at 6 months. Results: A total of 147 patients were referred for mitral valve repair, of which 114 patients were accepted for mitral valve repair by the local heart team. In total, 106 of the 114 patients underwent surgical intervention, 6 defaulted their surgical dates, and 2 refused surgery. Of those accepted for surgery, 57.9% were males, 42.1% were females, with a mean age of 47.7 years in both groups combined, 44.7% had hypertension, 43.9% were smokers and 21.1% had concomitant IHD; 56.1% were pre-operative NYHA functional class III, 29.8% were class II, 7% class IV, and 7% were class I; 60.2% had a 6-month post-operative NYHA functional class I, 32.3% had class II, 5.4% class III, and 2.2% had class IV. Mitral valve prolapse (MVP) with flail segment due to chord rupture was the predominant etiology (29%); P2 was the most common segment involved (36%), followed by A2 (29.8%). For MVP, including patients with infective endocarditis, the mortality rate was 4.8% at 30 days and 6 months. The overall mortality rates for all patients accepted for mitral valve repair were 4.7% and 6.6% at 30 days and 6 months respectively. Freedom from reoperation was 98% at 6 months. There was a significant association between bileaflet involvement and mitral valve repair failure (p=0.006). Chordal insertion with annuloplasty was the most common intervention used (45.5%). Conclusion: Mitral valve prolapse was the predominant etiology in patients referred for mitral valve repair. The mortality rate for mitral valve repair in the prolapse group was 4.8% at 6 months. Chordal insertion with annuloplasty was the most common intervention used. Bileaflet involvement was found to be an independent risk factor for repair failure. The mortality rate for all patients accepted for mitral valve repair was 6.6% at 6 months.